Hubungan antara kualitas pelayanan kesehatan dengan kepuasan pasien BPJS di Puskesmas Wenang - Wullur, Raetasya Rachelea Rinda; Sapulete, Margareth Rosalinda; Wariki, Windy Mariane Virenia (UNIVERSITAS SAM RATULANGI, 2023)
Background: It is important for healthcare centers to pay attention to their quality of care as it serves as a foundation in maintaining and enhancing care quality, for the sole purpose of increasing the overall health of the population. Over 93,47% of Indonesia’s population uses national health insurance administered by BPJS. SERVQUAL is used in this study to measure quality of care which consists of reliability, responsiveness, empathy, assurance, and tangibles.Aim: The objective of this research is to see if there is any relationship between quality of healthcare and BPJS patient’s satisfaction at Wenang Health Center, Manado city.Methods: Quantitative and analytical research is used in this study with cross sectional study design. Survey questionnaires were distributed to a total of 110 people who received healthcare in Wenang Health Center.Result: The result of this study indicates that there is a relationship between all dimensions of healthcare service quality and BPJS patient’s satisfaction.Conclusion: As such, Wenang Health Center should pay attention to all the dimensions of healthcare services as to give better care to BPJS patients and in return, increase the overall health of its community.Keywords: health service quality, patient’s satisfaction, BPJS